Differences between metabolically healthy and unhealthy obesity in PAI-1 level: Fibrinolysis, body size phenotypes and metabolism. Issue 180 (August 2019) - Basurto, Lourdes; Sánchez, Lucero; Díaz, Alma; Valle, Magdalena; Robledo, Ariadna; Martínez-Murillo, Carlos
Abstract: Background: Different studies have recognized the existence of subtypes of obesity and normal weight, in which it is reported that not all patients show the same cardiometabolic risk, called "metabolically healthy" and "metabolically unhealthy". In several reviews, differences in the inflammatory profile have been studied, but there is not information on the relationship of body size phenotypes with thrombosis risk. Objective: Determine the association between body size phenotypes and fibrinolytic activity by measuring the concentration of plasminogen activator inhibitor-1 (PAI-1). Methods: A cross-sectional study was conducted in women aged 40 to 65 years. Anthropometric measurements and biochemical determinations were performed on all participants. The fibrinolytic activity was determined by measuring PAI-1 by ELISA. Karelis criteria were used to define metabolic status. Four groups were formed: Metabolically healthy normal weight (MHNW), Metabolically unhealthy normal weight (MUNW), Metabolically healthy obese (MHO) and Metabolically unhealthy obese (MUO). Results: 230 women were included in our study with a mean age 52.3 ± 5.9 years. The concentration of PAI-1 showed a significant difference between the groups MHNW, MUNW, MHO, MUO [2.3 (0.08, 13.6), 12.7, (0.08, 33.1), 23.4 (2.6, 28.8) and 22.8 (2.0, 46.7) ng/mL, respectively, p  = 0.006]. Multiple regression analysis identified that BMI and HOMA-IR were independent factors influencing PAI-1 levels. Conclusion: This study is the first one that recognizes differences in the fibrinolytic activity between body size phenotypes. The groups with the lowest fibrinolytic activity were MUO and MHO, however, MUNW also present alterations of fibrinolysis, thus suggesting a prothrombotic state. Highlights: Some studies have recognized the existence of subtypes of obesity, in which a different cardiometabolic risk is reported. There is no information on the relationship of body size phenotypes with fibrinolytic activity. The objective of this study was to determine the association between body size phenotypes and PAI-1 level. PAI-1 level showed a significant differences between the groups metabolically healthy and unhealthy, normal weight and obese. The elevation of PAI-1 suggests an increased prothrombotic state.